2015
DOI: 10.4236/jpee.2015.39001
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Price Forecasting Problem and Techniques in Deregulated Electricity Markets

Abstract: In deregulated electricity markets, price forecasting is gaining importance between various market players in the power in order to adjust their bids in the day-ahead electricity markets and maximize their profits. Electricity price is volatile but non random in nature making it possible to identify the patterns based on the historical data and forecast. An accurate price forecasting method is an important factor for the market players as it enables them to decide their bidding strategy to maximize profits. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…A large number of competing methods exist to measure, model and predict energy price volatility, and it is important to note that no research has suggested any universal superiority of one method over the others. Instead, each method has merit and may work well in certain circumstances (Nomikos & Andriosopoulos, 2012;Sisodiaa et al, 2015;Singh & Mohanty, 2015). The results indicate a large variation in scientists' methodologies to address the issues in different countries (Sisodiaa et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 98%
“…A large number of competing methods exist to measure, model and predict energy price volatility, and it is important to note that no research has suggested any universal superiority of one method over the others. Instead, each method has merit and may work well in certain circumstances (Nomikos & Andriosopoulos, 2012;Sisodiaa et al, 2015;Singh & Mohanty, 2015). The results indicate a large variation in scientists' methodologies to address the issues in different countries (Sisodiaa et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 98%
“…The ARIMA forecasting model is the most common type of linear time series model based on Box-Jenkins methodology as presented in [11]. In most cases, the methodology does not require the estimation of many parameters to make the final choice of model [12].…”
Section: Related Previous Work Of Forecasting Modelmentioning
confidence: 99%
“…Note, that the problem of forecasting processes is relevant in solving many problems related to optimizing power systems. The extensive scientific literature is devoted to this problem [41][42][43][44][45][46][47][48]. The approach we use is only one of the possible approaches.…”
Section: Implementation Of the First Taskmentioning
confidence: 99%